Easy digital photography - Slaughter, Scott (Beginners series., 2000)
Learn about today's (and tomorrow's) digital imaging technology, image software, digital cameras and scanners in this newly revised edition. Do more with your photos that you ever thought possible by learning how to repair, enhance, add special effects and other tasks previously confined to the darkroom.